Direct proof of unconditional asymptotic consensus in the Hegselmann–Krause model with transmission‐type delay. Issue 5 (6th May 2021) - Haskovec, Jan
Abstract: We present a direct proof of asymptotic consensus in the non‐linear Hegselmann–Krause model with transmission‐type delay, where the communication weights depend on the particle distance in phase space. Our approach is based on an explicit estimate of the shrinkage of the group diameter on finite time intervals and avoids the usage of Lyapunov‐type functionals or results from non‐negative matrix theory. It works for both the original formulation of the model with communication weights scaled by the number of agents, and the modification with weights normalized a'la Motsch–Tadmor. We pose only minimal assumptions on the model parameters. In particular, we only assume global positivity of the influence function, without imposing any conditions on its decay rate or monotonicity. Moreover, our result holds for any length of the delay.